Catholics in the Soviet Union: New Research and New Sources on Everyday Religious Life (1917–1958) - Freeze, Gregory L. (The catholic historical review, 2020)
Until now research on religious in Soviet Russia has relied chiefly on documents generated by state, party, and police organs. As instruments of the regime's antireligious campaigns, these documents reflect official policy and reveal little about the everyday life of believers. To fill this gap in the documentation and historiography, the Russian Science Foundation has funded a three-year project to identify and publish documents from below—by tapping into those documents transmitted to the West and located in various institutional and private archives. In April 2020 the project organized a conference to discuss the initial results of this new undertaking.